"For in him the whole fullness of Deity dwells bodily": The Trinitarian Depths of the Incarnation. (December 2016) - Ormerod, Neil
This article explores further implications of Lonergan's four-point hypothesis, linking the trinitarian relations with four created participations in the divine nature, this time in the area of Christology. These include a much richer trinitarian account of the Incarnation, with a deeper pneumatological dimension emerging. It offers a brief comparison of this approach with three other approaches which similarly seek to provide a richer trinitarian account of Christology, from Christopher Schwöbel, Hans Urs von Balthasar, and David Coffey.